Social media news among Iraqi immigrants before and after immigration to Europe - Mohammed Ali, Hussein Saadi; Yasin, Megat Al-Imran; Alsagoff, Syed Agil; Mohamad, Ab.Halim (Gokmen Arslan, 2022)
This article discusses how Iraqi immigrants use social media to collect news for illegal immigration to Europe. Social media has a major and important role in the recent illegal migration of Iraqis to Europe. Because of the economic, political and security challenges that the Iraqis experienced during the period of confronting terrorism, it made the Iraqis think about emigrating and looking for other places to live in peace and far from crises and wars. The migrants used social media to obtain information on how to migrate and reach the destination country through the information provided by social media about immigration. Iraqi immigrants acquired participatory and deliberative skills in dealing with information and social media news about immigration, as well as the good timing of migration and the type of information related to immigration. The methodology of this research was based on the qualitative research method. Data were collected through in-depth individual interviews conducted with fifteen informants, those who previously had the experience of illegal immigration and are now in Iraq. The sampling technique has been reached with the "snowball" method.